2010
DOI: 10.1073/pnas.1005144107
|View full text |Cite
|
Sign up to set email alerts
|

Lack of both bradykinin B1 and B2 receptors enhances nephropathy, neuropathy, and bone mineral loss in Akita diabetic mice

Abstract: An insertion polymorphism of the angiotensin-I converting enzyme gene (ACE) is common in humans and the higher expressing allele is associated with an increased risk of diabetic complications. The ACE polymorphism does not significantly affect blood pressure or angiotensin II levels, suggesting that the kallikrein-kinin system partly mediates the effects of the polymorphism. We have therefore explored the influence of lack of both bradykinin receptors (B1R and B2R) on diabetic nephropathy, neuropathy, and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 59 publications
6
100
1
2
Order By: Relevance
“…Interestingly, kinins not only stimulate bone resorption, but also synergistically potentiate the bone resorptive effect of IL-1 (Lerner, 1991;Lerner and Modeer, 1991), by a mechanism dependent on prostaglandin production (Lerner et al, 1989). In contrast to these observations, it has been reported that mice lacking both subtypes of kinin receptors have decreased bone mass as assessed by dual emission x-ray absorptiometry (Kakoki et al, 2010). Since histomorphometric analysis was not performed, it is not possible to know if the decreased bone mass was a consequence of increased resorption or decreased formation of bone.…”
Section: Introductionmentioning
confidence: 52%
“…Interestingly, kinins not only stimulate bone resorption, but also synergistically potentiate the bone resorptive effect of IL-1 (Lerner, 1991;Lerner and Modeer, 1991), by a mechanism dependent on prostaglandin production (Lerner et al, 1989). In contrast to these observations, it has been reported that mice lacking both subtypes of kinin receptors have decreased bone mass as assessed by dual emission x-ray absorptiometry (Kakoki et al, 2010). Since histomorphometric analysis was not performed, it is not possible to know if the decreased bone mass was a consequence of increased resorption or decreased formation of bone.…”
Section: Introductionmentioning
confidence: 52%
“…In diabetic Akita mice with mutation in the insulin2 gene, the lack of bradykinin receptor1 (B1R) and receptor2 (B2R) (i.e. B1R/B2R double knockout) induces profound diabetic complications, including massive albuminuria, glomerulo sclerosis, reduction of nerve conduction velocity, and marked bone mineral loss [59] . It is thus possible that B1R/ B2R and their related kinin signaling participate in the DMinduced bone loss.…”
Section: Possible Mechanisms Of Dm-induced Osteoporosismentioning
confidence: 99%
“…Male mice, deficient in both B1 and B2 receptor, studied at 12 months of age, display mild hyperinsulinemia with normal glucose levels, indicating mild insulin resistance (Kakoki et al 2010). In ob/ob mice made deficient in both kinin receptors, mild hyperglycemia; enhanced insulin release; and hepatic abnormalities have been reported (Barros et al 2012b).…”
Section: Animal Studymentioning
confidence: 99%
“…TK gene therapy has been reported to reverse insulin resistance and attenuate nephropathy in diabetic rats (Yuan et al 2007). Moreover, lack of kininogen or kinin B2 receptor impaired insulin sensitivity and glucose tolerance in nondiabetic animals, indicating that the KKS is involved in insulin action and glucose homeostasis (Damas et al 1999, Duka et al 2001, Kakoki et al 2010.…”
Section: Introductionmentioning
confidence: 99%